Transitional cell carcinoma of urinary bladder along with pyometra in a female German Shepherd dog - Sharma, Deepti; Kumar, Amit; Kumar, Adarsh; Bodh, Deepti; Tyagi, S.P.; Sharma, Anjali (Indian Journal of Veterinary Surgery, 2026)
-